The Protection of Intellectual Property in Relations Between Entrepreneurs - Rzęsa, Hanna (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The Deputies’ bill amending the Labor Code and the Entrepreneurs’ Law provides for the extension of the legal definition of an employee to entities performing their duties personally for remuneration, permanently for the same entity, for a period of not less than 6 months. The proposed modification of the aforementioned definition will cause some changes not only in the field of regulations regarding employee rights, but also in the protection of intangible assets, such as intellectual property. In particular, the certain modifications will be visible in the way of copyright protection and fair competition between entrepreneurs. Even the inalienable nature of moral rights will not protect this sphere of the author’s rights from some transformations in the field of protection. The aim of the article is therefore to trace the current legal status, mainly based on the analysis of selected normative acts regarding labor law as well as intellectual property law and to try to answer the question of which legal status – current or postulated after the entry into force of the thematic amendment – would be more favorable in terms of protection of intangible assets that are part of the enterprise.